Entre Afrique du Nord et de l’Ouest, les relations transsahariennes à un moment charnière - Nora Mareï; Olivier Ninot (Bulletin de l’Association de Géographes Français)
The links between Mediterranean Africa and sub-Saharan Africa are old. In recent years, new dynamics have been consolidated, mainly in urban and coastal areas. They contribute to a renewal of economic interactions between Mediterranean, Sahara and Sahel, particularly in the western part, on which this article focuses. These changes fuel regionalisation processes, partly based on major infrastructure plans that support the development of maritime, land and air exchanges of goods and people between countries located in this West African space.